Strategies used by teachers in the implementation of positive discipline in primary schools in Gokwe north district. - Gumbo, John (Midlands State University, 2017)
The research study focused on the strategies used by teachers in the implementation of positive discipline in primary schools in Gokwe North District. The sample comprised of five schools where fifty teachers and five school heads participated in the research study. The mixed methods approach was used together with the descriptive survey design in carrying out the research. Probability sampling technique was adopted and stratified random sampling was used in the selection of research participants. To collect data school heads were involved during face to face interviews and teachers responded to questionnaires. The findings of the research study showed that teachers are using strategies such as parental involvement, counselling, corporal punishment, acceptable ways of communication, good classroom management and developing self-discipline in learners to implement positive discipline. Another finding made was that teachers need to be trained in positive discipline since this is a strategy new area to most teachers who should understand first before the implementation process. The implication of the study is that learners respond to positive discipline. From the research findings the researcher recommended that the Ministry of Primary and Secondary Education should come up with circulars which specify and standardise the strategies for the implementation of positive discipline in primary schools in the country as a whole. Also the benefits of positive discipline should be realised by all stakeholders who include among others learners, teachers and parents. Further, suitable provisions should be put in place such as appropriate infrastructure for counselling sessions and trained counsellors enrolled in schools. The government should make sure workshops are conducted training teachers on positive discipline nationwide.